Práticas de performance de Gilberto Gil ao violão em Expresso 2222 - Samy Erick Ferreira Félix (2020)
This dissertation’s main purpose is to analyze the performance practices used by Gilberto Gil on the guitar in the introduction of the song Expresso 2222. From the transcription of the version recorded in 1972 on the homonymous LP and its later versions (GIL, 1994, 2007, 2009, 2010a, 2010b and 2014), in which Gil added new instrumental excerpts to the introduction, comparative analyzes were made. It was used the mAAVm (Method of Analysis of Audio and Music Videos), proposed by BORÉM (2018 and 2016), and some of its tools: EdiP (Performance Edition), MaPA (Audiovisual Performance Map) and EdiPA (Edition of Audiovisual Performance). In addition, a pedagogical approach to the technical procedures used by Gilberto Gil in his introduction is presented. In a creative and also pedagogical aspect, a new instrumental introduction was composed by the author of this research, using some of the performance practices of Gil's definitive version. The research points to the “resfulêgo” da sanfona [bellows shake], an instrumental practice originated from accordion and widespread by Luiz Gonzaga in its Brazilian northeastern musical genres, as Gil's main influence in the elaboration of this instrumental introduction.